2013 IEEE Global Conference on Signal and Information Processing 2013
DOI: 10.1109/globalsip.2013.6737146
|View full text |Cite
|
Sign up to set email alerts
|

Efficient reconfigurable scheme for the recovery of sub-Nyquist sampled sparse multi-band signals

Abstract: Sub-Nyquist sampling makes use of sparsities in analog signals to sample them at a rate lower than the Nyquist rate. The reduction in sampling rate, however, comes at the cost of additional digital signal processing (DSP) which is required to reconstruct the uniformly sampled sequence at the output of the sub-Nyquist sampling analog-to-digital converter. At present, this additional processing is computationally intensive and time consuming and offsets the gains obtained from the reduced sampling rate. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Submitted to the IEEE Transactions on Signal Processing, 2015. This is an extension of a conference publication [90].…”
Section: Included Papersmentioning
confidence: 91%
“…Submitted to the IEEE Transactions on Signal Processing, 2015. This is an extension of a conference publication [90].…”
Section: Included Papersmentioning
confidence: 91%
“…We have observed that the problem of reconstructing missing samples is similar to that of the reconstruction problem in sub-Nyquist sampled sparse multi-band signals considered in [8]. Assume that the whole Nyquist band is divided into N sub-bands of equal width π/N.…”
Section: Proposed Reconstructormentioning
confidence: 99%
“…Parts of this work have been presented at a conference [18] where only the basic concept was outlined without giving any proofs. However, in order to get further insight and understanding of the efficient reconfigurable scheme, in Section IV we show that the reconstruction problem can be expressed in terms of the proposed analysis and synthesis FBs.…”
Section: A Contributions and Outline Of The Papermentioning
confidence: 99%
“…Based on this, we introduce a reconfigurable reconstruction scheme in Section V. Using complexity expressions for the proposed reconstructor and the polyphase implementation of the straightforward scheme in [7], we show that order-ofmagnitude reduction of the complexity is achievable using the proposed reconstructor. Furthermore, in [18], the filters in the analysis FB were designed using numerical optimization which can be time-consuming especially for higher filter orders and/or larger K. In Section VI of this paper, we propose a least-squares approach for designing these filters so that their filter coefficients can be obtained via a closed-form solution. In addition to reducing the design effort, the closedform solution enables us to redetermine the filter coefficients online, if required.…”
Section: A Contributions and Outline Of The Papermentioning
confidence: 99%
See 1 more Smart Citation